Cage rearing rhinopithecus roxellana feed in the breeding and lactating period and preparation method thereof - LI SHANGFEI; CHEN JIANGUO; HAN LI; XIAO YUNCAI; SHEN LIQUAN; LI XIANG; GUO AIZHEN (2015)
The present invention discloses a cage rearing rhinopithecus roxellana feed in the breeding and lactating period and a preparation method thereof. The cage rearing rhinopithecus roxellana feed comprises the following raw materials: corn, soybean meal, extruded soybeans, rice straws, alfalfa hay, oat hay, vitamins and trace element premix. The preparation method includes the following steps: A, weighing a certain proportion of calcium hydrogen phosphate, seven water ferrous sulfate, vitamin D3, vitamin K3, carriers, etc. and mixing the various raw materials evenly; B, weighing a certain proportion of the corn, the soybean meal, the extruded soybean, sucrose, edible salt, and peanut oil, and mixing the mixture evenly; C, weighing a certain proportion of the alfalfa hay, the oat hay, and the rice straws, crushing the above materials into grass meals, and mixing the grass meals evenly; and D, mixing the various raw materials in the step A, then adding the mixture in the step B and mixing evenly, then mixing evenly with the mixture in the step C, puffing and granulating the mixture to be peanut-shaped granules with a puffing coefficient of 1.2. The cage rearing rhinopithecus roxellana feed is comprehensive in nutrition, and can effectively stimulate the appetite of rhinopithecus roxellana, improve the feed intake of rhinopithecus roxellana, and improve the lactating capacity of rhinopithecus roxellana in the lactating period and body constitution and survival rate of young rhinopithecus roxellana.